1987
DOI: 10.1111/j.1752-7325.1987.tb02003.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the Effects of a Statewide Sealant Initiative on Dentists' Knowledge and Attitudes

Abstract: The effects of a statewide initiative promoting the use of dental sealants were evaluated by assessing dentists' knowledge and attitudes before the initiative and 18 months later. Immediate changes also were determined for participants in continuing education (CE) sessions, a principal component of the initiative. Results of these assessments indicate that minor improvements in knowledge and attitudes occurred, that the effects were stronger but still modest for those dentists who participated in CE sessions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The differing rates of study completion for those dentists achieving lower scores as compared to higher scores is of concern in the present study. Such response patterns could provide support for mandatory continuing professional education and has been noted by other authors (23). However, the selective withdrawal of some dentists from the study may indicate that they were working in non‐ideal circumstances that did not allow their ongoing involvement.…”
Section: Discussionsupporting
confidence: 84%
“…The differing rates of study completion for those dentists achieving lower scores as compared to higher scores is of concern in the present study. Such response patterns could provide support for mandatory continuing professional education and has been noted by other authors (23). However, the selective withdrawal of some dentists from the study may indicate that they were working in non‐ideal circumstances that did not allow their ongoing involvement.…”
Section: Discussionsupporting
confidence: 84%
“…The two general dentist regressions explained between 42 and 48 percent of the variance involved in the estimated level of sealant use. More variance was explained in this research than was evidenced in the 38 percent found in the Iowa study (7), the 21 percent in the Badner and Rosenberg study (S), and the 29 percent in the North Carolina study (9). No multiple regression research had been done previously with pediatric dentists; therefore, comparison with this study's pediatric dentist level of variance explained (between 42% and 46%) was not possible.…”
Section: Discussionmentioning
confidence: 68%
“…The North Carolina study revealed the importance of Knowledge and Attitude to the model. The overall intent of the North Carolina research was to evaluate its sealant education program's effectiveness (9). The number of variables studied was limited, therefore, and the resultant R was low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The followup questionnaire contained the same attitude, knowledge, and use questions. Four additional items from a previous initiative were used to assess practice changes in patient acceptance of sealants, respondents' perceptions of success or failure at increasing sealant use, and knowledge gained during the program year (15). Questionnairesand complete item results are available from the authors.…”
Section: Subjectsmentioning
confidence: 99%